Kritik Terjemahan: Sebuah Pengantar Pendek - Zafrialdi, M. (Humaniora, 2010)
Article presented the role and function of translation critics, preceded by analyzing a difference of translation results based on the men?s jobs, continued by clarifying the meaning and role of translation critics, translation analysis as one aspect in tranlation critics, and efforts to involve translation critics in education. It is concluded that translation critics is a bridge that correlate translation theory dan its practice, the importance of the critician.s attitude and his knowled in translation, the ability of a translation critician in comprehending and analysing the output of translation, and the advantage of involving translation critics in education.